Anti-TNF therapy: past, present and future. (19th November 2014) - Monaco, Claudia; Nanchahal, Jagdeep; Taylor, Peter; Feldmann, Marc
Abstract: While for a century therapeutics has been dominated by small molecules, i.e. organic chemicals of 400Da absorbable via the gut, this is no longer the case. There are now a plethora of important medicines which are proteins and injectable, which have dramatically improved the therapy of many inflammatory diseases and of cancer. Most of these are monoclonal antibodies, some are receptor Ig Fc fusion proteins, others are cytokines or enzymes. The key to this new aspect of therapeutics has been the filling of unmet needs, and the consequent commercial success, which promoted further research and development. The first 'biologic' for a common disease, rheumatoid arthritis (RA), was a monoclonal antibody, infliximab, to human tumour necrosis factor (TNF). This was based on our work, which is described in this review, summarizing how TNF was defined as a good target in RA, how it was developed is described here, as well as future indications for anti-TNF and related agents. Biologics are now the fastest growing sector of therapeutics.